Identification and development of source material for breeding early bushy and short-vined cultivars of Cucurbita moschata Duch. ex Poir. - A. G. Elatskova (Труды по прикладной ботанике, генетике и селекции, 2021)
Background. There are three species cultivated in Russia: Cucurbita pepo, C. maxima, and C. moschata, the latter being the most thermophilic among them. Cultivars of C. moschata are grown in southern regions, where a growing season of no less than 110–130 days is required. C. moschata has no bushy cultivars suitable for cultivation. The aim of this study was to search for, identify and develop source material of C. moschata for breeding early-ripening bushy and short-vined cultivars.Materials and methods. Accessions from the VIR collection, advanced cultivars, hybrids and lines of various generations served as research material. The study was based on the guidelines for studying and maintenance of the collection and for cucurbit crop breeding.Results. Source material was identified for breeding practice: early accessions (90–98 days) possessing high productivity and fruit quality, with good taste, namely ‘Early Butternut’, ‘Butternut’, ‘Waltham Butternut’; accession k-3549, ‘Orekhovy’, and accession k-4235; and mid-early accessions (104–105 days) ‘Palov-kadu’, and ‘Aydzu Аkkikudza’. They exceeded in productivity the early-ripening reference (cv. ‘Mariya’) by 26.7–130%, and matched the reference in fruit quality. Hybrids from the crosses of vined accessions with the bushy form KL 745 were studied. Bushiness is inherited monogenetically and controlled by the recessive bu (bush) gene. Identified for breeding were early (93–95 days) bushy lines (KL) with a stem length of 0.8–1.2 m: KL 648, KL 652 and KL 656. Their productivity was within 4.2–4.5 kg per plant (higher than the reference by 40–50%). In fruit quality they were on the reference level. Early (92–98 days) short-vined lines (KPL) were identified, with a stem length of 1.3–2.0 m: KPL 168, KPL 640 and KPL 680; their productivity ranged 4.9–6.8 kg per plant, and their fruit quality was good or excellent.